2001
DOI: 10.1016/s0014-2999(01)00832-9
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes potentiates acetylcholine-induced relaxation in rabbit renal arteries

Abstract: The response of rabbit renal arteries to acetylcholine and its endothelial modulation in diabetes were investigated. Acetylcholine induced concentration-related endothelium-dependent relaxation of renal arteries that was significantly more potent in diabetic rabbits G Ž . than in control rabbits. Pretreatment with N -nitro-L-arginine L-NOArg , indomethacin, or L-NOArg plus indomethacin induced partial inhibition of acetylcholine-induced relaxation. Inhibition induced by L-NOArg plus indomethacin was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
5
11
0
Order By: Relevance
“…Moreover, the incubation of diabetic arterial segments with indomethacin enhanced the contractile response to 5-HT, thus suggesting that the endothelial arachidonic acid derivative of the cyclooxygenase via in diabetic arteries has vasodilator influence (probably prostacyclin). Our results are in agreement with the decreased activity of vasoconstrictor prostanoids (Makino and Kamata, 1998;Miranda et al, 2000a,b) and the enhanced activity of vasodilator prostanoids (Okumura et al, 2000;Alabadí et al, 2001) that have been reported in diabetes. It could be hypothesised that, in the experimental conditions of the present study, the absence of the vasoconstrictor prostanoid would be the expression of a compensatory mechanism addressed to minimise the deleterious consequences of both the hyperreactivity of renal artery to 5-HT and the defective participation of NO.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, the incubation of diabetic arterial segments with indomethacin enhanced the contractile response to 5-HT, thus suggesting that the endothelial arachidonic acid derivative of the cyclooxygenase via in diabetic arteries has vasodilator influence (probably prostacyclin). Our results are in agreement with the decreased activity of vasoconstrictor prostanoids (Makino and Kamata, 1998;Miranda et al, 2000a,b) and the enhanced activity of vasodilator prostanoids (Okumura et al, 2000;Alabadí et al, 2001) that have been reported in diabetes. It could be hypothesised that, in the experimental conditions of the present study, the absence of the vasoconstrictor prostanoid would be the expression of a compensatory mechanism addressed to minimise the deleterious consequences of both the hyperreactivity of renal artery to 5-HT and the defective participation of NO.…”
Section: Discussionsupporting
confidence: 93%
“…The maximal contraction induced by 5-HT in the presence of L-NA was significantly lower in renal arteries from diabetic rabbits than in those from control rabbits, thus suggesting that NO was less effective at inhibiting diabetic than control arteries, indicating a lower modulatory role of NO in the diabetic state. Previously, we have reported that the arterial response induced by the NO donor sodium nitroprusside is similar in renal arteries from control and diabetic rabbits, thus indicating that the sensitivity of smooth muscle cells of renal arteries to NO is not altered in our diabetic rabbits (Alabadí et al, 2001).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…On the other hand, we have also reported alterations in the vascular response of diabetic animals to 5-hydroxytryptamine (Miranda et al, 2000a(Miranda et al, , 2002 and acetylcholine (Miranda et al, 2000b;Alabadí et al, 2001). The aim of the present study was to analyse the influence of alloxan-induced diabetes on the reactivity of the rabbit basilar artery to endothelin-1, including attention to endothelin-1 receptors and the endothelial modulatory mechanisms regulating this response.…”
Section: Introductionmentioning
confidence: 91%